Upaya Meningkatkan Hasil Belajar Siswa Kelas X TKJ Dalam Mata Pelajaran Sistem Komputer Dengan Media Pembelajaran VTA Berbasis Web: Efforts to Improve the Learning Outcomes of Class X Computer and Network Engineering Students in Computer Systems Subjects Using Web-Based VTA Learning Media - Chandra Anugrah Putra; Wahyu Triyono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The Covid-19 pandemic means that learning is carried out online using zoom meetings and also directly in class. It can be seen that teachers only deliver material using the lecture method and the implementation of learning activities is still monotonous, namely repetitive between the teacher and students. Another problem is the lack of interest in asking students when the teacher gives them the opportunity to ask questions about material they don't understand, which has an impact on students' learning outcomes. VTA learning is learning (Video Tutorials and Animations) so this learning media has web-based learning which is designed using HTML and in this media uses Video learning, Tutorials accompanied by images and also Animation Videos so that learning is more interesting and easy for students to understand. Based on data analysis carried out on student activities, it was obtained that student activity results increased in each cycle. In cycle I the score obtained was 67 with an average of 3.22 with a percentage of 55% in the Sufficient category and while in cycle II the student activity achievement score was 78 with an average of 3.66 and a percentage of 77%. This shows that using VTA media can make students more active in learning. It can be concluded that there is an increase in learning outcomes for Computer Systems using VTA media in class X TKJ 1 SMK Negeri 1 Kasongan.